2014
DOI: 10.2478/s11686-014-0308-1
|View full text |Cite
|
Sign up to set email alerts
|

First detection and molecular characterization of Echinococcus equinus in a Mule in Turkey

Abstract: Cystic echinococcosis is a zoonotic disease with a cosmopolital distribution. It is caused by the larval stages (metacestodes) of the parasite Echinococcus granulosus which infects different animal species. In this report, we present a case of E. granulosus infection in a mule and molecular characterization of the cyst. For this purpose parasite material was collected from the liver of a necropsied mule. DNA was isolated and PCR amplification of mitochondrial 12S rRNA as well as partial sequencing of mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…This may be because older donkeys have a higher rate of exposure to infective stages (27) The PCR amplification of the ND2 gene produced bands of expected length (299bp) which agrees with the results obtained in previous study (20). Sequencing of amplified products showed the homology of these isolates to the reference sequence of E.equinus accessed in the Genbank which confirmed that equids are the specific intermediate host for E.equinus (1,(15)(16)(17)(18)(19)(20)(21). On the other hand, (7,22) have reported that horses can be infected with E.granulosus s.s. (sheep strain) as well as by E.equinus (horse strain).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This may be because older donkeys have a higher rate of exposure to infective stages (27) The PCR amplification of the ND2 gene produced bands of expected length (299bp) which agrees with the results obtained in previous study (20). Sequencing of amplified products showed the homology of these isolates to the reference sequence of E.equinus accessed in the Genbank which confirmed that equids are the specific intermediate host for E.equinus (1,(15)(16)(17)(18)(19)(20)(21). On the other hand, (7,22) have reported that horses can be infected with E.granulosus s.s. (sheep strain) as well as by E.equinus (horse strain).…”
Section: Discussionmentioning
confidence: 54%
“…These include two sheep strains (G1 and G2), two bovid strains (G3 and G5), a horse strain (G4), a camel strain (G6), two pig strains (G7 and G9) and cervid strains (G8 and G10) (5,13,14). E.equinus (also known as E. granulosus G4 or horse strain) uses equids as specific intermediate hosts (1,5,7,(15)(16)(17)(18)(19)(20)(21). No human cases of infection with E.equinus are known, and the epidemiological evidence suggests that it may be non-pathogenic to humans (13,15).…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports about E. granulosus strains circulating in Turkey. E. granulosus sensu stricto (G1-G3 complex), E. canadensis (G6 and G7 genotypes), and E. equinus (G4) have been reported both in livestock and humans (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Since Kumaratilake et al [ 9 ] based upon morphology described the occurrence of the equine strain in a naturally infected zebra in Southwestern Africa, data concerning similar infections in intermediate hosts other than horses are becoming increasingly common. Cases of infection in donkeys have been described in Egypt [ 10 ] and Tunisia [ 11 ], while Simsek and Cevik [ 12 ] reported its occurrence in a mule in Turkey. E. equinus was recently molecularly characterized for the first time in a zebra ( Equus burchellii ) and a lemur ( Varecia rubrai ) in the UK [ 13 ].…”
mentioning
confidence: 99%
“…There are few reports concerning the occurrence of E. equinus in Asia. Two cases of dogs harboring this species have been reported in Jordan [ 21 ] and Kyrgyzstan [ 20 ], while Simsek and Cevik [ 12 ] reported its presence in a mule in Turkey. The finding of a fertile E. equinus hydatid cyst in a donkey as well indicates that the species is most likely well established in the country.…”
mentioning
confidence: 99%